A phase 1 study of vorinostat maintenance after autologous transplant in high-risk lymphoma. Issue 4 (April 2015) - Hofmeister, Craig C.; Williams, Nita; Geyer, Susan; Hade, Erinn M.; Bowers, Mindy A.; Earl, Christian T.; Vaughn, John; Bingman, Anissa; Humphries, Kristina; Lozanski, Gerard; Baiocchi, Robert A.; Jaglowski, Samantha M.; et al.
Abstract Only a minority of patients with high risk lymphoma will be cured with autologous transplant, so maintenance with vorinostat, an oral agent with activity in relapsed lymphoma, was studied starting day + 60 for 21 consecutive days followed by a week off for up to 11 cycles. Twenty-three patients with lymphoma were treated. Ten patients completed the full 11-cycle treatment plan per protocol, four patients were removed due to progressive disease and seven withdrew or were removed from the study due to toxicities. Despite Prevnar vaccine administration every 2 months for three injections, the mean antibody concentration never reached protective levels (> 0.35 μg/mL). Fatigue and functional well-being measured by Brief Fatigue Inventory and Functional Assessment of Cancer Therapy-General improved significantly from cycle 1 to cycle 7, but depression scores from the Center for Epidemiologic Studies Depression scale did not change. Given the toxicities observed, this broad-spectrum deacetylase inhibitor at this schedule is not optimal for prolonged maintenance therapy.